KELUARNYA NEW ZEALAND SEBAGAI KEANGGOTAAN ANZUS 1985 - Selly Dwi Suryanti, Made (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol. 1, No. 1, 2012)
The disappointment felt by Australia and New Zealand to the United of Kingdom to make the two countries that really have to have a good relationship has chosen to be in the American defense umbrella to form alliances and to approach a covenant Trilateral security cooperation called ANZUS in 1951. However, because the New Zealand Prime Minister David Lange that is derived from the labor party has anti-nuclear policy should he realized in his country. This causes a slight disturbance in the alliance, where there is disagreement between the United State and New Zealand warship linked to by Americans who want to put into the area of New Zealand. This problem led to New Zealand should remain at its founding to keep running the anti-nuclear policy and decided to get out of the ANZUS alliance.